THEORETICAL FUNDAMENTALS OF FORMATION FORECASTING SKILLS OF FUTURE TEACHERS - E.M. Michayl (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the theoretical principles of forming of future teachers' prognostic skills.